Breast cancer burden in the United States (1990–2021) with a 15-year forecast: a comprehensive analysis based on the global burden of disease 2021 - Huang, Zhijian; Zhang, Lingxiao; Liu, Peizhang; Lin, Hongxiang; Peng, Zeyi; Zheng, Peixin; Sun, Xinhao; Lin, Lisheng (Frontiers in Oncology, 2025)
ObjectiveBreast cancer (BC) is one of the most common cancers globally, placing a significant social burden. This study estimates the BC burden in the U.S. from 1990 to 2021 and projects future trends for the next 15 years.MethodsUsing data from the Global Burden of Disease (GBD) 2021 study, we analyzed four measures: prevalence, incidence, death, and disability-adjusted life years (DALYs), stratified by sex, age, U.S. states, and socio-demographic index (SDI).ResultsBC burden in the U.S. has decreased, with reductions in age-standardized rates of prevalence, incidence, mortality, and DALYs for both sexes. The overall age-standardized prevalence rate dropped from 695.0 (653.5–741.5)/100,000 in 1990 to 556.0 (525.2–584.7)/100,000 in 2021. The ASIR declined from 68.3 (65.1–70.3)/100,000 to 51.7 (48.4–54.1)/100,000. Death rates fell from 15.9 (14.9–16.5)/100,000 to 9.4 (8.5–9.9)/100,000, while DALYs decreased from 485.1 (462.9–507.0)/100,000 to 277.4 (260.1–294.8)/100,000 over the same period. Burden varies by state and SDI: in 2021, low-SDI states, Kentucky and Louisiana had the highest prevalence and incidence, while Louisiana and Mississippi had the highest mortality. Projections suggest a continued downward trend through 2036.ConclusionsBC burden in the U.S. decreased overall, but disparities persist across sex, age groups, and states with varying SDI levels. Addressing risk factors and improving healthcare access are essential to further reduce BC burden.